Pengaruh Penerapan Model Pembelajaran Scramble terhadap Kemampuan Menulis Kalimat Sederhana Siswa Kelas II SDN 02 Pariangan - Hasibuan, Rahma Maulidina; Fathia, Wilda (CV Berkah Syahdin Trust, 2026)
The background of this research is based on the low writing ability of students, particularly in composing simple sentences that conform to proper and correct Indonesian language structures. The Scramble learning model was chosen because it can motivate students to think actively and construct sentences systematically from scrambled words. This study aims to determine the influence of the Scramble learning model on the ability to write simple sentences of Grade II students at SDN 02 Pariangan. This research is a quantitative study with a pre-experimental approach using the one-group pretest-posttest design. The population in this study consists of all Grade II students at SDN 02 Pariangan, totaling 17 students, consisting of 11 boys and 6 girls. The research instrument was a writing performance test, assessed based on five indicators: complete and clear sentence structure, correct use of spelling, meaningful and understandable sentences, sentences written sequentially to form a coherent story, and appropriate and easily understood vocabulary. The data analysis techniques included normality test, homogeneity test, paired sample t-test, and N-Gain analysis to examine the significance of the differences before and after the treatment. The results of the study indicate an improvement in the ability to write simple sentences after the implementation of the Scramble learning model. This is evidenced by the increase in the average score from 55.82 in the pretest to 84.41 in the posttest. The improvement is also supported by the N-Gain score of 0.7035, which falls into the high category, and the N-Gain percentage of 70.35%, which is considered effective. Based on the results of the t-test, the significance value (Sig. 2-tailed) was 0.000, which is lower than the significance level of 0.05. Therefore, H0 is rejected and H1 is accepted, indicating that there is a significant effect of using the Scramble learning model on the ability to write simple sentences among second-grade students at SDN 02 Pariangan.